2019
DOI: 10.1016/j.cropro.2019.104865
|View full text |Cite
|
Sign up to set email alerts
|

Use of unmanned aircraft systems (UAS) and multispectral imagery for quantifying agricultural areas damaged by wild pigs

Abstract: Use of unmanned aircraft systems (UAS) and multispectral imagery for quantifying agricultural areas damaged by wild pigs" (2019).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Validations of classified imagery, or ground truthing, further improve confidence in drones as a detection method for feral horse damage, as they revealed 69.5% and 70.1% accuracies of classified imagery for April 2019 and December 2020, respectively. Comparatively, similar validations for the semi‐automated classification of wild pig damage in agricultural fields using RGB imagery led to estimates of 74%–94% accuracy (Fischer et al, 2019). The higher accuracies in the study involving wild pigs were likely due to the homogenous agricultural landscape where damage stands out better; pigs knocked down large regions of corn, leaving flat and discoloured areas.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Validations of classified imagery, or ground truthing, further improve confidence in drones as a detection method for feral horse damage, as they revealed 69.5% and 70.1% accuracies of classified imagery for April 2019 and December 2020, respectively. Comparatively, similar validations for the semi‐automated classification of wild pig damage in agricultural fields using RGB imagery led to estimates of 74%–94% accuracy (Fischer et al, 2019). The higher accuracies in the study involving wild pigs were likely due to the homogenous agricultural landscape where damage stands out better; pigs knocked down large regions of corn, leaving flat and discoloured areas.…”
Section: Discussionmentioning
confidence: 94%
“…The use of drones for the assessment of animal pest impacts on an environment is relatively new, with most past studies focussing on agricultural damage from feral animals rather than their impacts to protected areas (e.g. national parks; Fischer et al, 2019, Pla et al, 2019). Drones have, however, been well‐used for the assessment of the extent and damage of plant pest species in protected areas, and found to be an effective way to assess damage and change over time (Hill et al, 2017; Müllerová et al, 2017; Perroy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This article provides an integrated drone solution to capture multi-spectral images with geotagging, which has important reference value in terrain and scene perception. Fischer et al (2019) combined multi-spectral and drone technology and used feature extraction algorithms to detect cornfield areas damaged by wild boar. This yields a new monitoring technology that effectively acquires terrain information and assesses the damage of crops based on its description.…”
Section: Multi-spectral Imaging Technologymentioning
confidence: 99%
“…Recent research has focused on drones and object detection technology to monitor timing and extent of wild pig damage at a field scale (Michez et al 2016, Kuzelka and Surovy 2018, Rutten et al 2018, Samiappan et al 2018, Fischer et al 2019). Approaches to train and fully automate classification of wild pig damage include crop height models (Michez et al 2016, Kuzelka and Surovy 2018), vegetation indices calculated from multispectral drone imagery (Houborg and McCabe 2016, Fischer et al 2019), and textural feature extractions (Samiappan et al 2018, Fischer et al 2019). Studies concluded that drone approaches were a useful tool to efficiently estimate wild pig damaged areas in crops, yet when it came to determining yield losses, an approximate estimate based on regional yield averages was used (Rutten et al 2018).…”
mentioning
confidence: 99%
“…Samiappan et al 2018, Fischer et al 2019, Foster 2021). However, Rutten et al (2018) found a higher average loss (17.2%) toT A B L E 4a Total loss of income due to wild pig damage.…”
mentioning
confidence: 99%